2023
DOI: 10.3390/diagnostics13010140
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal-Microbiome Analysis by 16S Sequencing and Real-Time PCR in Patients from Novosibirsk (Russia) with Cervical Lesions and Several Years after Cancer Treatment

Abstract: Disturbed cervicovaginal-microbiome (CVM) structure promotes human papillomavirus (HPV) persistence and reflects risks of cervical lesions and cancer onset and recurrence. Therefore, microbiomic biomarkers may be useful for cervical disease screening and patient management. Here, by 16S rRNA gene sequencing and commercial PCR-based diagnostic kits, we profiled CVM in cytological preparations from 140 HPV-tested women (from Novosibirsk, Russia) with normal cytological findings, cervical lesions, or cancer and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…It was further confirmed that the depletion of Lactobacillus and the increase in specific anaerobes (such as Megasphaera , Prevotella and Gardnerella ) were related to cervical lesions [ 24 ]. LEfSe analysis identified cancer-specific vaginal biomarkers, including Mycoplasma , Bacillus , Bacteroides , Dialister , Peptoniphilus , Porphyromonas , Anaerococcus , Prevotella , and Sneathia , and the HPV + biomarker Bifidobacterium distinguished them from the control; the reliability of the experimental findings has been confirmed by other studies [ 13 , 27 29 ]. Bifidobacterium is a beneficial microorganism of the intestinal flora that has many functions, such as resisting harmful bacteria, exerting antitumour, increasing immunity and improving gastrointestinal function, and it also exists in the oral cavity and vagina [ 30 ].…”
Section: Discussionsupporting
confidence: 68%
“…It was further confirmed that the depletion of Lactobacillus and the increase in specific anaerobes (such as Megasphaera , Prevotella and Gardnerella ) were related to cervical lesions [ 24 ]. LEfSe analysis identified cancer-specific vaginal biomarkers, including Mycoplasma , Bacillus , Bacteroides , Dialister , Peptoniphilus , Porphyromonas , Anaerococcus , Prevotella , and Sneathia , and the HPV + biomarker Bifidobacterium distinguished them from the control; the reliability of the experimental findings has been confirmed by other studies [ 13 , 27 29 ]. Bifidobacterium is a beneficial microorganism of the intestinal flora that has many functions, such as resisting harmful bacteria, exerting antitumour, increasing immunity and improving gastrointestinal function, and it also exists in the oral cavity and vagina [ 30 ].…”
Section: Discussionsupporting
confidence: 68%
“…For example, L. crispatus turned out to be the predominant Lactobacillus species in women with normocenosis for the ASCUS and LSIL groups, while L. iners prevailed in the HSIL group. There are contradictions in the works of other authors concerning L. iners: some studies show that it accompanies HPV infection and SIL (Wang et al, 2019;Sasivimolrattana et al, 2022;Xu et al, 2022), whereas other studies demonstrate no association of the kind (McKee et al, 2020;Gomez Cherey et al, 2023;Ivanov et al, 2023). L. crispatus is considered to protect from SIL progressing in HPV (Cheng et al, 2020), since it produces a lot of the D-isomer of lactic acid which increases the viscosity of the vaginal secrete and elevates its ability to sequester virions, in contrast to L. iners which produces only the L-isomer (Kalia et al, 2020;Nicolò et al, 2023).…”
Section: Discussionmentioning
confidence: 77%
“…It was further con rmed that the depletion of Lactobacillus and the increase of speci c anaerobes (such as Megasphaera, Prevotell and Gardnerella vaginalis) were related to cervical lesions [25]. LEfSe analysis identi ed cancer-speci c vaginal biomarkers including Mycoplasma, Bacillus, Bacteroides, Dialister, Peptoniphilus, Porphyromonas, Anaerococcus, Prevotella, Sneathia, and for HPV + biomarker is bi dobacterium distinct them from control, the reliability of experimental ndings are con rmed by other studies [13,[28][29][30]. Bi dobacterium is a bene cial microorganism of intestinal ora, which has many functions such as resisting harmful bacteria, providing nutrition, anti-tumor, anti-aging, enhancing immunity and improving gastrointestinal function, it also exists in the oral cavity and vagina [31].…”
Section: Discussionmentioning
confidence: 89%